Resolución de problemas como estrategia metodológica en las leyes de Kepler aplicada al proceso de enseñanza-aprendizaje a estudiantes de tercer año de BGU - Macas Chalco, Nashely Berenice (2024)
Nowadays, the intention is to develop skills and creativity in students, for this, methodological strategies must be adjusted to the topics covered and to the different contexts in which students find themselves. This research aims to analyze problem-solving as a methodological strategy in Kepler's laws applied to the teaching-learning process in high school, which has a qualitative approach, with documentary design, using the method of literature review whose instruments were the search log and bibliographic cards; the results show the importance of the application of this methodological strategy, its characteristics and how to apply it. Finally, it is concluded that problem-solving as a methodological strategy allows developing critical thinking skills, reinforcing autonomy through collaborative work, as well as the importance of the teacher proposing or choosing optimal problems for the development of learning. Keywords: strategies, problem solving, teaching, learning, Kepler's laws